2015
DOI: 10.3346/jkms.2015.30.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Three-month Treatment Response and Exacerbation in Chronic Obstructive Pulmonary Disease

Abstract: The aim of this study was to investigate relationships between acute exacerbation and Forced Expiratory Volume 1 second (FEV1) improvement after treatment with combined long-acting beta-agonist (LABA) and inhaled corticosteroid (ICS) in patients with chronic obstructive pulmonary disease (COPD). A total of 137 COPD patients were classified as responders or nonresponders according to FEV1 improvement after 3 months of LABA/ICS treatment in fourteen referral hospitals in Korea. Exacerbation occurrence in these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…AEs were assessed at the clinic every 3 months, where possible. Moderate AE was defined as a clinic visit, while severe AE was defined as hospitalization or an emergency room visit owing to one or more of the following: worsening of dyspnea, increased sputum volume and purulent sputum [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…AEs were assessed at the clinic every 3 months, where possible. Moderate AE was defined as a clinic visit, while severe AE was defined as hospitalization or an emergency room visit owing to one or more of the following: worsening of dyspnea, increased sputum volume and purulent sputum [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fletcher and Peto ( 1 ) reported that the degree of airflow obstruction was a predictor of mortality. FEV 1 is used as the main parameter in the evaluation of many aspects of COPD ( 2 ). Dyspnea is also a useful measure of COPD, because this symptom is closely related to the patient's the quality of life.…”
Section: Introductionmentioning
confidence: 99%